Evaluation of the marginal fit of full contoured zirconia, lithium disilicate and metal crowns fabricated using CAD-CAM: An in vitro study - Savitha Dandekeri; Fowzaan Feroz; Sanath K Shetty; Mohammed Zahid; Uma Prabhu; Ragher Mallikarjuna (Wolters Kluwer Medknow Publications, 2023)
Introduction: The marginal fit of any dental restoration is vital to its long-term success. Lack of adequate fit is potentially detrimental to both the tooth and the supporting periodontal tissues. The purpose of this study was to evaluate the marginal fit of monolithic zirconia, monolithic lithium disilicate and monolithic metal crowns and compare the three groups. Methods: The study was conducted by fabricating ten samples for each group, total of 30 samples. A premolar stainless steel die was used to standardize the preparation. PVS putty material was used to make impressions of the model and was poured using type IV die stone. The samples were all fabricated using CAD-CAM. The marginal gap was measured by SEM, and the results were analysed using SPSS software. Results: The mean marginal gap of zirconia, metal and lithium disilicate crowns was 79.49 μm, 46.83 μm and 70.79 μm, respectively. Discussion: The metal group showed the lowest marginal gap among the groups. This difference in marginal fit is due to the sintering process where the organic binders in soft metal burn out and the metallic powder particles are being sintered (caked) without creating a fused phase. Clinical Significance: Marginal fit plays a very important role in the long-term success of a crown. Discrepancy in marginal fit results in food and plaque accumulation causing caries and periodontal breakdown, eventuating the failure of the restoration. A perfect marginal fit would enhance the longevity of any indirect restoration. Knowledge about which indirect restoration has the best marginal fit is critical.